(untitled) (International journal of artificial intelligence, 2024)
This article explores the integration of sciences in education, focusing on the interdisciplinary connections in chemistry and other related disciplines. It highlights the importance of integrating various scientific fields to foster a holistic understanding of complex phenomena. The paper discusses the benefits of interdisciplinary approaches in education, such as promoting critical thinking, enhancing problem-solving skills, and fostering a deeper appreciation for the interconnectedness of scientific disciplines. Examples of integrated lessons and projects are provided to illustrate the practical application of interdisciplinary concepts in the classroom. Overall, the paper emphasizes the significance of interdisciplinary connections in enriching the educational experience and preparing students for future scientific endeavors.